2010
DOI: 10.1111/j.1442-2050.2009.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiation therapy practice for advanced esophageal carcinoma in Africa

Abstract: While numerous surveys of pattern of practices of palliative radiotherapy (RT) in advanced esophageal cancers have been published in developed countries, there is no such survey in African countries. During and after a regional training course by the International Atomic Energy Agency (IAEA) in palliative cancer care, a questionnaire was distributed to African RT centers to gather information about infrastructure and human resources available, and the pattern of practice of palliative RT for esophageal cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results showed that accelerated treatment at reduced doses (30 Gy) is feasible with all considered energies. Furthermore, it is interesting to note that using higher energies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) it is also possible to administer a higher dose with less hypofractionated fractionation (36 Gy, 2.4 Gy/fraction).…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that accelerated treatment at reduced doses (30 Gy) is feasible with all considered energies. Furthermore, it is interesting to note that using higher energies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15) it is also possible to administer a higher dose with less hypofractionated fractionation (36 Gy, 2.4 Gy/fraction).…”
Section: B Amentioning
confidence: 99%
“…The standard treatment technique of pancreatic cancer is three-dimensional conformal radiotherapy 3 . However, the technique is not available in several centers, especially in developing countries, where the only available technique is standard two-dimensional (2D), often based on a cobalt unit (Co60) [4][5][6] . For the 2D technique, guidelines for adjuvant or radical treatments involving prophylactic nodal irradiation (PNI) are available 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment technique of CAP is three-dimensional conformal radiotherapy (3D-CRT), intensity modulated radiotherapy, and stereotactic radiotherapy ( 3 ). These techniques however, are not available in several centers, especially in developing countries, where the only available technique is standard two-dimensional (2D) technique, often based on a cobalt unit ( 4 – 6 ). For 2D technique, guidelines for adjuvant or radical treatments involving the prophylactic irradiation of regional lymph nodes are available ( 7 ).…”
Section: Introductionmentioning
confidence: 99%